Tax incentives, bequest motives, and the demand for life insurance: evidence from a natural experiment in Germany*. (1st October 2015) - SAUTER, NICOLAS; WALLISER, JAN; WINTER, JOACHIM
Abstract This paper studies the role of taxation and bequest motives in households' demand for life insurance. We develop a stylized three-period life cycle model of life insurance demand and test its predictions regarding tax changes and bequests motives. An unexpected halving of the tax exemption limit for interest and dividend income in Germany allows us to identify the impact of changes in taxation on the demand for life insurance in a difference-in-differences setting. In line with our theoretical predictions, we document that ownership of life insurance products increased significantly among households affected by the reform. We also find some evidence of a more pronounced response among households with stronger bequest motives.